Hydro‐mechanical response of collapsible soils under different infiltration events. (3rd February 2015) - Rotisciani, G. M.; Sciarra, G.; Casini, F.; Desideri, A.
Summary The behavior of a partially saturated soil during surface‐water infiltration is analyzed by means of an elasto‐plastic constitutive model formulated in terms of effective stress and extended to unsaturated conditions. The model is calibrated considering laboratory‐scale experimental results under suction‐controlled conditions. The wetting process in two collapsing soils, initially loaded at in situ stresses, is simulated by imposing two different boundary conditions: surface ponding and water flow. The stress paths resulting from the imbibition process are analyzed at different points inside the layer. Copyright © 2015 John Wiley & Sons, Ltd.